Heterogeneous base catalysts for edible palm and non-edible Jatropha-based biodiesel production - Lee, Hwei Voon; Juan, Joon Ching; Abdullah, Nurul Fitriyah; Md Fahmy, Rabiah Nizah; Yap, Taufiq Yun Hin (Chemistry Central, 2014)
Background: Transesterification catalyzed by solid base catalyst is a brilliant technology for the noble process featuring the fast reaction under mild reacting condition in biodiesel production. Heterogeneous base catalysts are generally more reactive than solid acid catalysts which require extreme operating condition for high conversion and biodiesel yield. In the present study, synthesis of biodiesel was studied by using edible (palm) or non-edible (Jatropha) feedstock catalyzed by heterogeneous base catalysts such as supported alkali metal (NaOH/Al2O3), alkaline-earth metal oxide (MgO, CaO and SrO) and mixed metal oxides catalysts (CaMgO and CaZnO). Results: The chemical characteristic, textural properties, basicity profile and leaching test of synthesized catalysts were studied by using X-ray diffraction, BET measurement, TPD-CO2 and ICP-AES analysis, respectively. Transesterification activity of solid base catalysts showed that > 90% of palm biodiesel and > 80% of Jatropha biodiesel yield under 3 wt.% of catalyst, 3 h reaction time, methanol to oil ratio of 15:1 under 65°C. This indicated that other than physicochemical characteristic of catalysts; different types of natural oil greatly influence the catalytic reaction due to the presence of free fatty acids (FFAs). Conclusions: Among the solid base catalysts, calcium based mixed metal oxides catalysts with binary metal system (CaMgO and CaZnO) showed capability to maintain the transesterification activity for 3 continuous runs at ~ 80% yield. These catalysts render high durability characteristic in transesterification with low active metal leaching for several cycles.